UAE Foreign Policy-Making Structures - Hussein, Mohammed H.; Abdulmageed, Lubna R. (Humanities Journal of University of Zakho, 2017)
The study of the concept of foreign affairs has always been an interesting subject for politicians, researchers and academics alike, as the sequence of events and how they develop help to understand how a certain country may utilize certain methods to deal with certain events. The foreign affairs policies of the UAE can be understood through its generally stable internal affairs and the philosophy implemented by the government body in which the most suitable goals can be chosen, adding into consideration regional and international factors. In truth, there are several positive factors that influence foreign affairs policies of the UAE, including rich oil reserve and strategically important geography, having borders overlooking the Arabian Gulf and the Indian Ocean which gave the UAE an important and active regarding international trade. to study the nature of the foreign affairs of an county, one have to understand the foundationson which decisions are made, including legislative authority, judicial authority and executive authority. This study was divided into a preface and two chapters; the main subject of the preface is "Establishment of the UAE and its Constitution", while Chapter One of the study tackled "Offical Foundations of UAE Decision Making" and Chapter Two explained the "Un offical Foundations of UAE Decision Making".